Enhancing Students' Reading Comprehension Through Two Stay Two Stray (TSTS) Technique - Asdar Asdar (Jurnal Pendidikan dan Pengajaran, 2021)
Reading is one of the techniques in learning that is often involved in classroom practices, and Two Stay Two Stray is one of the methods introduced in the cooperative learning process. This study aims to find out how the Two Stay Two Stray technique improved students' reading comprehension. This research focused on applied classroom action research. The population of this research was the students of the English Education Department. This research was used to take one class as the research sample, which consists of 32 students.  The instrument of this research was a multiple-choice test. There are two cycles in this research. The result shows that students' mean score in cycle 1 was 59,68 and in cycle 2 was 75,31. Based on the results, the Two Stay Two Stray technique was successful. Therefore, it can be inferred that the Two Stay Two Stray technique strengthened the students' reading comprehension. In addition, the students were more interested and inspired to join the class, and they were excited during the teaching-learning process, based on the results of the observation sheet.